Produktifitas Penggunaan Waktu Kerja Perawat di Instalasi Rawat Inap Rumah Sakit Ahmad Yani Pekanbaru - Andra, Fithriyah; Ismainar, Hetty (KESMARS: Jurnal Kesehatan Masyarakat, Manajemen dan Administrasi Rumah Sakit, 2018)
Performance has an important position in management and organization. One dimension in the performance benchmark is the use of time in work. The work time of the nurse is the pattern of working time utilization for the nursing activity in accordance with the main task and its function in accordance with the job description that is 80 percent. The purpose of this study is to describe the productivity of the nurses working time in the hospital. The method in this reseach is qualitative approach which conducted by observation participation to create a description of the working time usage. Data collection techniques use observation sheets and interview guides and document tracking. In this research, there are 6 informants namely Head of Nursing, Nursing Coordinator and 4 nurses. Data analysis using triangulation. Result, The forms of nurse activity consist of: productive nursing (direct and indirect), personal and non-productive activities. Show that the use of productive work time of nurse is 42,4 percent (that is direct activity 19,6 percent and indirect nursing activity 22,8 percent) and non productive 57,6 percent. Conclusion the productivity of nurse work time is not optimal and more dominated by non productive activities such as: talking outside the main task, watching TV, using gadgets or outdoors for other activities. Keyword: Hospital, Nurse, Productivity, Working time